Effects of dealloying and heat treatment parameters on microstructures of nanoporous Pd. (1st July 2020) - Chen, Y.Z.; Ma, X.Y.; Zhang, W.X.; Dong, H.; Shan, G.B.; Cong, Y.B.; Li, C.; Yang, C.L.; Liu, F.
Abstract: Microstructures of nanoporous Pd are essentially important for its physical and chemical properties. In this work, we show that the microstructures of nanoporous Pd can be tuned by adjusting compositions of the precursor alloys, and dealloying and heat treatment parameters. Both the ligament and pore sizes decrease with increasing the electrochemical potential upon dealloying and the concentration of noble component in the precursor alloys. Heat treatment causes coarsening of the nanoporous structure. Above a critical temperature, the nanoporous structures are subjected to significant coarsening. Below the critical temperature, surface diffusion is believed to dominate the coarsening process. Above the critical temperature, the nanoporous structure coarsens remarkably at a rather high rate, which is ascribed to a multiple-mechanism controlled process.